Preparation method of nitrogen-doped graphene CIGS thin film battery tail gas purifying agent
Through the synergistic effect of nitrogen-doped graphene carrier and composite copper source, the problem of low removal efficiency of H2S and H2Se in the exhaust gas of CIGS thin film batteries is solved, efficient purification of room temperature is achieved, and the stability and application value of the purifier are improved.
Patent Information
- Application Number
- CN202411293859.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-14
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2044-09-14
AI Technical Summary
The prior art is difficult to efficiently remove H2S and H2Se gases in the exhaust gas of CIGS thin film solar cells at room temperature, and traditional desulfurization agents have problems of low desulfurization efficiency and poor stability.
Using nitrogen-doped graphene carrier and composite copper source as purifiers, the removal efficiency of H2S and H2Se is improved through the synergistic effect of ammonia water and strong alkali solution, the active site and specific surface area of the carrier are enhanced, and through Fe3+ and Cu2+ The bimetallic coupling system enhances desulfurization performance.
The efficient removal rate of H2S and H2Se is achieved, with a conversion rate of no less than 93.5% and 92%, which improves the stability and application value of the purifier.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the field of preparation of environmentally friendly materials, specifically to the field of room-temperature high-efficiency purification materials, and in particular to a method for preparing a nitrogen-doped graphene CIGS thin-film battery tail gas purifier. Background Art
[0002] Solar energy, as a clean, efficient and inexhaustible new energy source, has always been an important part of the country's sustainable development strategy. As a new type of photovoltaic cell, copper indium gallium selenide (CIGS) thin-film solar cells have multiple advantages of high efficiency, low cost and long life, and can make full use of my country's abundant indium resources, so they have a bright future. In CIGS thin-film solar cells, the CIGS absorption layer plays a vital role.
[0003] During the preparation of the CIGS absorption layer, a sulfurization process is often used after selenization is completed to dope S atoms on the surface of the film to replace some Se atoms, thereby adjusting the energy band, widening the band gap, and increasing the open circuit voltage. The method used to dope S atoms is to expose the device to an atmosphere filled with H2S / N2 mixed gas to achieve recrystallization. At regular intervals, the excess H2S / N2 mixed gas will be discharged as waste gas, and the waste gas also contains a small amount of H2Se gas replaced by S. The H2S and H2Se contained in these mixed gases are both highly toxic gases, which will seriously endanger people's health and cause serious environmental pollution. They need to be purified before they can be discharged.
[0004] In order to remove acidic gases such as H2S, people have developed a variety of desulfurization agents and desulfurization methods, such as activated carbon method, metal oxide method, etc. However, most traditional desulfurization agents often require a higher operating temperature to achieve a higher desulfurization efficiency when used. However, the temperature of the exhaust gas discharged from the production of CIGS thin-film batteries is room temperature. If traditional desulfurization agents are used as exhaust gas purifiers, there is a problem of low desulfurization efficiency. Copper-based desulfurizers have a high sulfur capacity at room temperature and can meet the basic requirements of efficient desulfurization at room temperature. However, there are defects such as easy reduction of divalent copper and low stability when used alone. In order to improve the stability of copper-based desulfurizers, it is often necessary to load copper-based substances in a carrier with a porous structure, but there is still a problem of uneven loading due to insufficient active sites on the carrier, which leads to low desulfurization efficiency.
[0005] Patent publication number CN 112958078A discloses a CIGS tail gas treatment purifier and a preparation method thereof. The purifier prepared in this application includes hydrotalcite, and the hydrotalcite is impregnated and loaded with permanganate ions, which can meet the requirements of low-temperature and efficient removal of H2S and H2Se. However, the reaction process will release heat. If the heat is not dissipated in time, the bed temperature will increase, thereby affecting the tail gas purification performance of the purifier. In addition, the problem of insufficient active sites in the hydrotalcite leading to insufficient loading has not been solved. Patent CN publication number 109439376B discloses a room temperature desulfurizer and a preparation method thereof. The desulfurizer prepared in this application includes γ-alumina, nano zinc oxide, transition metal oxides and rare earth metal oxides. The transition metal is copper oxide, and the room temperature desulfurization effect is best when the rare earth metal is lanthanum oxide. However, no improvement has been made on the stability of the metal oxides, and there are still hidden dangers of reduced desulfurization efficiency and poor durability.
[0006] Therefore, there is an urgent need in the market for a nitrogen-doped graphene CIGS thin-film battery exhaust gas purifier that can efficiently remove H2S and H2Se gases at room temperature. Summary of the invention
[0007] In view of the problems existing in the prior art, the present invention selects nitrogen-doped graphene carrier and composite copper source as the main components of the purifier, and then adds ammonia water and strong alkaline solution to prepare a nitrogen-doped graphene CIGS thin-film battery exhaust purifier, which has the advantage of efficiently removing H2S and H2Se gases at room temperature.
[0008] In order to achieve the above object, the technical solution adopted by the present invention is as follows: On the one hand, the present invention provides a method for preparing a nitrogen-doped graphene CIGS thin film battery tail gas purifier, comprising the following steps: S1. Place the nitrogen-doped graphene carrier and the composite copper source in a reaction kettle, add ammonia water, stir for 20-40 minutes, and obtain a reaction product for standby use; S2. Add a strong alkaline solution to the reaction product of step S1, stir for 20-30 minutes, wash, filter, and dry to obtain a nitrogen-doped graphene CIGS thin film battery exhaust purifier.
[0009] In some embodiments of the present invention, the method for preparing the nitrogen-doped graphene carrier comprises the following steps: (1) dissolving graphene oxide, phenylboric acid and adenine in deionized water, stirring for 20-40 min, adding a methanol solution of cobalt nitrate hexahydrate, stirring for 20-40 min, heating to 130-150° C., stirring for 4-6 h, and obtaining product 1 for later use; (2) cooling the product 1 of step (1) to room temperature, distilling under reduced pressure, drying, and calcining under an inert atmosphere to obtain a product 2 for standby use; (3) Dissolve xylan in citric acid solution, stir for 50-70 min, add product 2 of step (2), sonicate, wash, and dry to obtain a nitrogen-doped graphene carrier.
[0010] In some embodiments of the present invention, in step (1), the mass ratio of graphene oxide to adenine is 1:(2-5); in step (3), the mass ratio of product 2 to xylan is 1:(31-35).
[0011] Preferably, the mass ratio of graphene oxide to adenine is 1:(3-5); in step (3), the mass ratio of product 2 to xylan is 1:(31-33).
[0012] More preferably, the mass ratio of graphene oxide to adenine is 1:4; in step (3), the mass ratio of product 2 to xylan is 1:33.
[0013] Graphene oxide is often used as a carrier of metal or non-metallic materials due to its advantages such as large specific surface area, strong mechanical strength, strong flexibility and stable properties. The hole structure inside its molecules enables it to have a good purification effect on H2S and H2Se gases. However, the stacking of graphene oxide sheets has limited purification effect on H2S and H2Se gases and loading effect on metal ions.
[0014] On the one hand, the applicant doped graphene oxide with adenine as a nitrogen source, phenylboric acid as an auxiliary carbon source and a boron source. By replacing C atoms with N and B, the active sites on the graphene oxide were increased, and the bonding between the composite copper source and the carrier was enhanced, thereby improving the removal performance of the composite copper source for H2S gas. In addition, the imidazole group in adenine and Cu 2 + The coordination effect occurs between the carrier and the composite copper source, thereby increasing the binding force between the carrier and the composite copper source and improving the desulfurization efficiency of the purifier. Furthermore, the applicant introduces cobalt nitrate hexahydrate, and the graphite layer doped with N and Co 2+ A Co-N complex is formed between the interfaces of the two, which enhances the electron transfer at the interface of the composite material, thereby increasing the loading activity of the carrier and effectively improving the desulfurization efficiency of the purifier. On the other hand, the applicant composites xylan with N, Co, and B-doped graphene oxide, and uses the hydroxyl and carboxyl groups in xylan to cross-link with the groups on the surface of graphene oxide, thereby forming a carrier structure with a larger specific surface area and improving the stability of graphene oxide. Furthermore, the xylan molecular chain contains many hydroxyl groups, which can adsorb metal ions in the composite copper source, thereby improving the removal efficiency of the purifier for H2S and H2Se gases.
[0015] In some embodiments of the present invention, the method for preparing the composite copper source comprises the following steps: 1) Mix ferric nitrate hexahydrate and ethylene glycol, and stir at 50-60° C. for 20-30 minutes to obtain a mixture 1 for later use; 2) Mix triethylamine nitrate and copper nitrate, stir for 5-10 minutes, heat to 60-70°C and stir for 2-4 hours to obtain mixture 2 for later use; 3) Take the mixture 1 of step 1), add the mixture 2 of step 2), and stir for 30-50 minutes to obtain a composite copper source.
[0016] In some embodiments of the present invention, the molar ratio of the ferric nitrate hexahydrate to the copper nitrate is (0.2-0.6):1.
[0017] Preferably, the molar ratio of the ferric nitrate hexahydrate to copper nitrate is 0.4:1.
[0018] Both copper-based and iron-based desulfurizers have high desulfurization capacity at room temperature and are good desulfurizers for treating acidic substances such as H2S in CIGS thin-film battery exhaust gas. However, copper-based substances alone are easily reduced to form elemental copper, and iron-based substances alone have the disadvantages of low desulfurization strength and easy powderization when exposed to water, both of which will lead to reduced desulfurization performance.
[0019] On the one hand, the applicant uses Fe 3+ and ethylene glycol as raw materials to prepare a low eutectic solvent, Fe 3+ It can directly undergo redox reaction with H2S and the product Fe 2+ The purifier can be regenerated by oxygen oxidation, which makes it have the advantage of cyclic regeneration, and the hexahydrated ferric nitrate and ethylene glycol produce hydrogen bonds with coordination effect, so that the low eutectic solvent can be stably present and play a role; on the other hand, the applicant uses triethylamine nitrate and copper nitrate to prepare an ionic liquid, which is environmentally friendly and has the characteristics of both amine and nitrate. The amine group is conducive to the improvement of the alkalinity of the system, thereby promoting the 2+ The removal of H2S gas, and the amine group and Fe in triethylamine nitrate 3+ The coordination between them is beneficial to Fe 3+ and Cu 2+ A bimetallic coupled desulfurization system is formed, which can synergistically remove acidic gases such as H2S and improve the desulfurization efficiency of the purifier; further, the applicant selects a low eutectic solvent and an ionic liquid as a medium to transfer Fe 3+ and Cu 2+ Introducing nitrogen-doped graphene into the carrier is beneficial to improving the dispersion of metal ions in the carrier, thereby improving the desulfurization activity of the metal ions, thereby improving the removal efficiency of the purifier for H2S and H2Se gases.
[0020] In some embodiments of the present invention, the mass ratio of the nitrogen-doped graphene carrier to the composite copper source in step S1 is 1:(0.6-1).
[0021] Preferably, in step S1, the mass ratio of the nitrogen-doped graphene carrier to the composite copper source is 1:0.8.
[0022] In some embodiments of the present invention, in step S1, the mass ratio of the composite copper source to aqueous ammonia is 1:(0.8-1.2), and the concentration of aqueous ammonia is 3-5 mol / L.
[0023] Preferably, in step S1, the mass ratio of the composite copper source to the ammonia water is 1:1, and the concentration of the ammonia water is 4 mol / L.
[0024] In some embodiments of the present invention, the strong alkaline solution in step S2 is a sodium hydroxide solution with a concentration of 1-2 mol / L.
[0025] In some embodiments of the present invention, the mass ratio of the composite copper source to the strong alkaline solution is 1:(0.2-0.3).
[0026] Preferably, the mass ratio of the composite copper source to the strong alkaline solution is 1:0.25.
[0027] On the other hand, the present invention also provides a nitrogen-doped graphene CIGS thin-film battery exhaust gas purifier obtained by the preparation method described in the above technical scheme, wherein the conversion rate of H2S is not less than 93.5%, and the conversion rate of H2Se is not less than 92%.
[0028] Compared with the prior art, the present invention has the following beneficial effects: (1) The present invention selects nitrogen-doped graphene carrier and composite copper source as the main components of the purifier, and then adds ammonia water and strong alkaline solution to prepare a nitrogen-doped graphene CIGS thin film battery exhaust purifier. Through the synergistic effect between the components, the purifier has the advantage of efficiently removing H2S and H2Se gases at room temperature.
[0029] (2) The present invention dopes graphene oxide with N, B, and Co, and composites it with xylan to prepare a nitrogen-doped graphene carrier. By increasing the active sites and specific surface area of graphene oxide, the carrier can better combine with the copper source, thereby improving the removal efficiency of H2S and H2Se gases.
[0030] (3) The present invention uses Fe 3+ Prepared deep eutectic solvent and Cu 2+ The prepared ionic liquid mixture uses the amine group in triethylamine nitrate and Fe 3+ Coordination occurs between them to form Fe 3+ and Cu2+ The bimetallic coupled desulfurization system further improves the removal efficiency of the purifier for H2S and H2Se gases.
[0031] (4) The nitrogen-doped graphene CIGS thin-film battery exhaust gas purifier prepared by the present invention has the characteristics of efficiently removing H2S and H2Se gases at room temperature, can be widely used in the field of room-temperature high-efficiency purification materials, and has good commercial application value. DETAILED DESCRIPTION
[0032] The present invention will be described below in conjunction with specific embodiments. It should be noted that the following embodiments are examples of the present invention and are only used to illustrate the present invention, but not to limit the present invention. Other combinations and various modifications within the concept of the present invention may be performed without departing from the spirit or scope of the present invention.
[0033] In the following examples, except for the nitrogen-doped graphene carrier and the composite copper source, the other compound monomers and related reagents used can be purchased from the market, among which xylan was purchased from Hebei Jiuxing Chemical Products Co., Ltd.
[0034] Preparation Example 1 The synthesis method of the nitrogen-doped graphene carrier A comprises the following steps: (1) 0.2 g of graphene oxide, 0.5 g of phenylboric acid and 0.8 g of adenine were dissolved in 80 ml of deionized water, stirred for 30 min, 40 ml of 30 wt% cobalt nitrate hexahydrate methanol solution was added, stirred for 30 min, heated to 140 ° C, stirred for 5 h, and product 1 was obtained for later use; (2) Cooling the product 1 to room temperature, distilling under reduced pressure, drying at 80°C for 12 h, and calcining at 800°C for 1 h under N2 to obtain the product 2 for later use; (3) Dissolve 33 g of xylan in 100 ml of 10 wt% citric acid solution, stir for 60 min, add 1 g of the product 2 of step (2), ultrasonicate for 30 min, wash with deionized water three times, and dry at 60 °C for 12 h to obtain nitrogen-doped graphene carrier A.
[0035] Preparation Example 2 The specific implementation manner of the nitrogen-doped graphene carrier B is the same as that of the nitrogen-doped graphene carrier A, except that in step (1), the mass of adenine is replaced with 0.36 g.
[0036] Preparation Example 3 The specific implementation manner of nitrogen-doped graphene carrier C is the same as that of nitrogen-doped graphene carrier A, except that in step (3), the mass of xylan is replaced with 30.5 g.
[0037] Preparation Example 4 The synthesis method of the composite copper source A comprises the following steps: 1) Mix 0.04 mol of ferric nitrate hexahydrate and 60 ml of ethylene glycol, and stir at 55°C for 25 min to obtain a mixture 1 for later use; 2) Mix 20 g of triethylamine nitrate and 0.1 mol of copper nitrate, stir for 10 min, heat to 65 °C and stir for 3 h to obtain mixture 2 for later use; 3) Take the mixture 1 of step 1), add the mixture 2 of step 2), and stir for 40 minutes to obtain the composite copper source A.
[0038] Preparation Example 5 The specific implementation manner of the composite copper source B is the same as that of the composite copper source A, except that in step 1), the molar number of ferric nitrate hexahydrate is replaced with 0.015 mol.
[0039] Preparation Example 6 The specific implementation manner of composite copper source C is the same as that of composite copper source A, except that in step 1), the molar number of ferric nitrate hexahydrate is replaced with 0.07 mol. Example
[0040] A method for preparing a nitrogen-doped graphene CIGS thin-film battery tail gas purifier comprises the following steps: S1. Place 10 g of nitrogen-doped graphene carrier A and 8 g of composite copper source A in a reaction kettle, add 8 g of 4 mol / L ammonia water, stir for 30 min, and obtain a reaction product for standby use; S2. Add 2 g of 1.5 mol / L sodium hydroxide solution to the reaction product of step S1, stir for 25 min, wash with deionized water 3 times, filter, and dry at 30° C. for 24 h to obtain a nitrogen-doped graphene CIGS thin film battery exhaust purifier. Example
[0041] A method for preparing a nitrogen-doped graphene CIGS thin-film battery tail gas purifier comprises the following steps: S1. Place 10 g of nitrogen-doped graphene carrier A and 6 g of composite copper source A in a reaction kettle, add 4.8 g of 3 mol / L ammonia water, stir for 20 min, and obtain a reaction product for standby use; S2. Add 1.2 g of 1 mol / L sodium hydroxide solution to the reaction product of step S1, stir for 20 min, wash with deionized water 3 times, filter, and dry at 30° C. for 24 h to obtain a nitrogen-doped graphene CIGS thin film battery exhaust purifier. Example
[0042] A method for preparing a nitrogen-doped graphene CIGS thin-film battery tail gas purifier comprises the following steps: S1. Place 10 g of nitrogen-doped graphene carrier A and 10 g of composite copper source A in a reaction kettle, add 14.4 g of 5 mol / L ammonia water, stir for 40 min, and obtain a reaction product for standby use; S2. Add 3.6 g of 2 mol / L sodium hydroxide solution to the reaction product of step S1, stir for 30 min, wash with deionized water 3 times, filter, and dry at 30° C. for 24 h to obtain a nitrogen-doped graphene CIGS thin film battery exhaust purifier. Example
[0043] The present invention provides a method for preparing a nitrogen-doped graphene CIGS thin-film battery tail gas purifier. The specific implementation manner is the same as that of Example 1, except that the mass of the composite copper source A in step S1 is replaced with 5 g. Example
[0044] The present invention provides a method for preparing a nitrogen-doped graphene CIGS thin-film battery tail gas purifier. The specific implementation manner is the same as that of Example 1, except that the mass of the composite copper source A in step S1 is replaced with 12 g. Example
[0045] The present invention provides a nitrogen-doped graphene CIGS thin-film battery tail gas purifier and a preparation method thereof. The specific implementation manner is the same as that of Example 1, except that the nitrogen-doped graphene carrier A is replaced by an equal amount of a nitrogen-doped graphene carrier B. Example
[0046] The present invention provides a nitrogen-doped graphene CIGS thin-film battery tail gas purifier and a preparation method thereof. The specific implementation manner is the same as that of Example 1, except that the nitrogen-doped graphene carrier A is replaced by an equal amount of a nitrogen-doped graphene carrier C. Example
[0047] The present invention provides a nitrogen-doped graphene CIGS thin-film battery tail gas purifier and a preparation method thereof. The specific implementation manner is the same as that of Example 1, except that the composite copper source A is replaced by the composite copper source B in equal amounts. Example
[0048] The present invention provides a nitrogen-doped graphene CIGS thin-film battery tail gas purifier and a preparation method thereof. The specific implementation manner is the same as that of Example 1, except that the composite copper source A is replaced by an equal amount of a composite copper source C.
[0049] Comparative Example 1 This comparative example provides a nitrogen-doped graphene CIGS thin-film battery exhaust gas purifier and a preparation method thereof. The specific implementation manner is the same as that of Example 1, except that graphene is used instead of the nitrogen-doped graphene carrier A.
[0050] Comparative Example 2 This comparative example provides a nitrogen-doped graphene CIGS thin film battery exhaust gas purifier and a preparation method thereof. The specific implementation method is the same as that of Example 1, except that copper hydroxide is used instead of the composite copper source A.
[0051] The nitrogen-doped graphene CIGS thin film battery exhaust gas purifier described in the above Examples 1-9 and Comparative Examples 1-2 was tested for the removal of H2S and H2Se gases at room temperature. The test results are shown in Table 1.
[0052] The removal of H2S and H2Se gases by the purifier at room temperature is determined by the tail gas treatment performance test: The dried nitrogen-doped graphene CIGS thin-film battery exhaust gas purifier is crushed and ground to obtain a 100-mesh powder. The powder is then placed in a mold of a tablet press and pressed into a sheet material at 10 MPa. The sheet material is briefly cut into smaller flakes, mixed evenly with 100-mesh quartz sand at a mass ratio of 1:1, and then placed in the experimental area of the reaction tube.
[0053] Then, CIGS industrial simulated tail gas (N2 / H2S / H2Se mixed gas, H2S=3000ppm, H2Se=500ppm, and the rest is N2) is directly introduced into the reaction tube at 500ml / min for purification. Finally, the hose at the outlet of the reaction tube is introduced into the tail gas absorption device (40wt% NaOH solution), the main gas valve is closed, and the flow meter is adjusted to zero.
[0054]
[0055] It can be seen from the data in Table 1 that the nitrogen-doped graphene CIGS thin-film battery exhaust gas purifier in Examples 1-3 of the present invention has the characteristics of high H2S and H2Se conversion rates. Among them, Examples 4-5 changed the reaction ratio between the nitrogen-doped graphene carrier and the composite copper source, so that the composite copper source was not fully loaded in the nitrogen-doped graphene carrier, and could not stably play the role of desulfurization, resulting in a decrease in the H2S and H2Se conversion rates; Examples 6-7 changed the nitrogen doping ratio during the preparation of the nitrogen-doped graphene carrier and the loading ratio between xylan and nitrogen-doped graphene, so that the active sites and specific surface area of graphene oxide were reduced, thereby reducing the H2S and H2Se conversion rates; Examples 8-9 changed the Fe in the composite copper source. 3+ and Cu 2+ The ratio of , which reduces the synergistic effect between metals, resulting in a significant decrease in the conversion rate of H2S and H2Se; Comparative Example 1 and Comparative Example 2 respectively selected graphene and copper hydroxide to replace nitrogen-doped graphene carrier A and composite copper source A. Tests found that the H2S and H2Se conversion rates of the prepared CIGS thin-film battery exhaust purifiers showed poor results.
[0056] The above implementation modes are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with this technology to understand the content of the present invention and implement it, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a nitrogen-doped graphene CIGS thin film battery tail gas purifier, characterized in that The following steps are involved: S1. Place the nitrogen-doped graphene carrier and the composite copper source in a reaction kettle, add ammonia water, stir for 20-40 minutes, and obtain a reaction product for standby use; S2. Add a strong alkaline solution to the reaction product of step S1, stir for 20-30 minutes, wash, filter, and dry to obtain a nitrogen-doped graphene CIGS thin film battery exhaust purifier.
2. The method for preparing a nitrogen-doped graphene CIGS thin film battery tail gas purifier according to claim 1, characterized in that: The preparation method of the nitrogen-doped graphene carrier comprises the following steps: (1) dissolving graphene oxide, phenylboric acid and adenine in deionized water, stirring for 20-40 min, adding a methanol solution of cobalt nitrate hexahydrate, stirring for 20-40 min, heating to 130-150° C., stirring for 4-6 h, and obtaining product 1 for later use; (2) cooling the product 1 of step (1) to room temperature, distilling under reduced pressure, drying, and calcining under an inert atmosphere to obtain a product 2 for standby use; (3) Dissolve xylan in citric acid solution, stir for 50-70 min, add product 2 of step (2), sonicate, wash, and dry to obtain a nitrogen-doped graphene carrier.
3. The method for preparing a nitrogen-doped graphene CIGS thin film battery tail gas purifier according to claim 2, characterized in that: In the step (1), the mass ratio of graphene oxide to adenine is 1:(2-5); in the step (3), the mass ratio of product 2 to xylan is 1:(31-35).
4. The method for preparing a nitrogen-doped graphene CIGS thin film battery tail gas purifier according to claim 1, characterized in that: The preparation method of the composite copper source comprises the following steps: 1) Mix ferric nitrate hexahydrate and ethylene glycol, and stir at 50-60° C. for 20-30 minutes to obtain a mixture 1 for later use; 2) Mix triethylamine nitrate and copper nitrate, stir for 5-10 minutes, heat to 60-70°C and stir for 2-4 hours to obtain mixture 2 for later use; 3) Take the mixture 1 of step 1), add the mixture 2 of step 2), and stir for 30-50 minutes to obtain a composite copper source.
5. The method for preparing a nitrogen-doped graphene CIGS thin film battery tail gas purifier according to claim 4, characterized in that: The molar ratio of the ferric nitrate hexahydrate to the copper nitrate is (0.2-0.6):
1.
6. The method for preparing a nitrogen-doped graphene CIGS thin film battery tail gas purifier according to claim 1, characterized in that: In the step S1, the mass ratio of the nitrogen-doped graphene carrier to the composite copper source is 1:(0.6-1).
7. The method for preparing a nitrogen-doped graphene CIGS thin film battery tail gas purifier according to claim 1, characterized in that: In step S1, the mass ratio of the composite copper source to the ammonia water is 1:(0.8-1.2), and the concentration of the ammonia water is 3-5 mol / L.
8. The method for preparing a nitrogen-doped graphene CIGS thin film battery tail gas purifier according to claim 1, characterized in that: The strong alkaline solution in step S2 is a sodium hydroxide solution with a concentration of 1-2 mol / L.
9. The method for preparing a nitrogen-doped graphene CIGS thin film battery tail gas purifier according to claim 8, characterized in that: The mass ratio of the composite copper source to the strong alkaline solution is 1:(0.2-0.3).
10. A method for preparing a nitrogen-doped graphene CIGS thin film battery tail gas purifier prepared by the method according to any one of claims 1 to 9, characterized in that: The H2 The conversion rate of S is not less than 93.5%, and the conversion rate of H2Se is not less than 92%.
Citation Information
Patent Citations
Graphene-zinc-oxide transparent conducting thin film and preparation method thereof
CN103199126A
Preparation method and application for carbon nanotube counter electrode thin film material modified by nitrogen-doped graphene quantum dots and graphene oxide
CN103500661A
Copper ferrite / carbon nanofiber / nitrogen-doped graphene composite electrocatalytic material
CN108607594A
Electrocatalyst with sandwich structure, and preparation method and application thereof
CN112968184A
Preparation and regeneration method of bimetallic Fe-Cu-BTC desulfurizer
CN116173924A
